2014
DOI: 10.17795/ajcmi-19214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tuberculosis Infection Among Health-Care Workers in Hamadan, West of Iran

Abstract: Background:The risk of occupationally acquired tuberculosis (TB) remains a concern, even now that the infection has been under control to a great extent. Objectives: The aim of this study was to ascertain the prevalence of latent TB infection and pulmonary TB, and to assess the risk factors for TB, among health care workers in Hamadan. Patients and Methods: Tuberculin skin test was performed on 245 health care workers, in two educational hospitals. The reaction was considered as "positive" if the induration di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Worldwide studies have revealed that the diagnostic value of ADA in extra pulmonary TB has been associated with controversial results (6)(7)(8)(9)(10). The present study demonstrated that the measured levels of ADA could be an acceptable contributing index in the diagnosis of extra pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide studies have revealed that the diagnostic value of ADA in extra pulmonary TB has been associated with controversial results (6)(7)(8)(9)(10). The present study demonstrated that the measured levels of ADA could be an acceptable contributing index in the diagnosis of extra pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TB remains a major health problem in many parts of the world (1,3,5). Almost one third of the world population (around 2 billion people) are infected with TB and are at risk to develop active pulmonary TB (1,3,6). Every year about 9 million people develop active TB and 1.5 to 2 million people die of the disease (1).…”
Section: Introductionmentioning
confidence: 99%
“…A low prevalence of LTBI (1.8%) was reported among medical and nursing students in Iran [22]. In contrast, a high prevalence of LTBI (38 to 49%) has been previously reported among HCWs in Iran [8,9,11,12]. These studies were conducted in general hospitals and evaluated LTBI among nurses, ward sisters, physicians, and service workers, most of whom have close contact with patients.…”
Section: Discussionmentioning
confidence: 99%
“…TB remains a major public health problem in Iran [ 1 ] The prevalence of latent TB infections (LTBI) among HCWs in Iran has been reported to range from 2 to 49% [ 8 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saha et al (2016) observed 61% severe pneumonia in Bangladeshi children. Hashemi et al (2014) worked on prevalence of tuberculosis and recorded 38% positive tuberculin test. Above two results were found much higher than the present study records.…”
Section: Prevalence Of Air Borne Diseases (%)mentioning
confidence: 99%